Older people's out-of-home mobility and wellbeing in Australia: Personal, built environment, and transportation factors associated with unmet mobility needs - Ma, Tracey; Kobel, Conrad; Ivers, Rebecca (Frontiers in Public Health, 2023)
Out-of-home mobility is fundamental to older people’s wellbeing and quality of life. Understanding the unmet mobility needs of older people is a necessary starting point for determining how they can be supported to be mobile. This study estimates the extent of unmet mobility needs among older Australians and identifies the characteristics of those most likely to report unmet mobility needs. Analysis was conducted on nationally representative data of 6,685 older Australians drawn from the 2018 Survey of Disability, Ageing and Carers conducted by the Australian Bureau of Statistics. Twelve predictor variables from two conceptual frameworks on older people’s mobility were included in the multiple logistic regression model. Twelve percent (n = 799) of participants had unmet mobility needs, and associated factors significant in multivariable models included being among the ‘young-old’, having a lower income, having lower levels of self-rated health, having a long-term condition, being limited in everyday physical activities, experiencing a higher level of distress, being unlicenced, having decreased public transport ability, and residing in major cities. Efforts to support older people’s mobility must make equity an explicit consideration, reject a one-size-fits-all approach, and prioritise the accessibility of cities and communities.